Catalytic activity of Ni3Mo surfaces for hydrogen evolution reaction: A density functional theory approach - Pham, Nguyet N. T.; Kang, Sung Gu; Kim, Hyoung-Juhn; Pak, Chanho; Han, Byungchan; Lee, Seung Geol (ELSEVIER, 2021)
Ni3Mo alloys are promising non-platinum group metal catalyst candidates for hydrogen evolution reactions in alkaline solution. The Volmer step for the hydrogen evolution reaction in alkaline medium was examined using density functional theory (DFT). We examined hydrogen adsorption on Ni3Mo surfaces [(0 0 1), (0 2 0), (1 0 0), and (1 0 1)]. Ni3Mo(1 0 1) showed the fastest dissociation of water in the first step of the HER among the investigated Ni3Mo surfaces. Hydrogen atom chemisorption was a key reaction that determines HER performance; the adsorption free energies revealed that Ni3Mo(1 01) has a higher electrocatalytic activity than the other surfaces of Ni3Mo. Our work provides insight into the excellent HER catalytic performance of Ni3Mo in alkaline solution and is expected to inform the design of efficient binary non-PGM catalyst for the HER.
Keywords: GENERALIZED GRADIENT APPROXIMATION; TOTAL-ENERGY CALCULATIONS; NI-MO ALLOY; EXCHANGE CURRENT; ALKALINE; EFFICIENT; ELECTROCATALYSIS; OXIDATION; ELECTROLYSIS; PERFORMANCE